Attitudes Towards Gender Equality in Soccer in the School Context in Spain (EAIGFU): design and evaluation of its psychometric properties - Pedro Gil-Madrona; Luz Marina Méndez-Hinojosa; Magaly Cárdenas-Rodríguez; María Delgado (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Even though the number of women playing soccer in Europe has expanded tremendously, the conception of soccer as an essentially masculine activity is still under investigation. Despite the importance, a study on the development and validation of a scale focusing on gender equality has not yet been reported. This study validates the Attitudes Towards Gender Equality Scale for School Football Soccer (EAIGFU). We utilized a non-experimental, cross-sectional design and a non-probabilistic sampling technique. The scale was applied to a sample of 883 Spanish students majoring in physical education. The average age of the students who participated in the study was 10.68 years (SD = .74). The sample was divided randomly into two groups to perform the analysis in two steps: a) exploratory factor analysis in Group 1 and b) confirmatory factor analysis in Group 2. The results showed that the three correlated factors model fitted the data in a good way [χ2/df = 2.09, GFI = .97, CFI = .93, NFI = .87, RMSEA = .05 CI 90% (.04, .06), and SRMR = .06]. Reliability by Cronbach's alpha was acceptable to good (.70 to .81). On the other hand, the links between the level of competence and egalitarian attitudes in soccer were reviewed and the beliefs and attitudes based on gender. It is concluded that EAIGFU is reliable, shows evidence of validity among Spaniard students of physical education, and the three correlated factors model is adequate to represent the equality between gender in football soccer.